Larval and pupal morphology of three species of the genus Psammoecus Latreille (Coleoptera: Silvanidae: Brontinae) in Japan with reference to the number of larval instars - Yoshida, Takahiro; Hirowatari, Toshiya (Zootaxa, 2015)
The last instar larva and the pupa of Psammoecus scitus Yoshida & Hirowatari, all instar larvae of P. simoni Grouvelle, and the last instar larva of P. hiranoi Yoshida & Hirowatari are described, and their morphologies are compared among species and instars. Larval association for P. simoni was confirmed by DNA barcoding. Apart from a brief description of the pupa of Cryptamorpha brevicornis (White) illustrated by Hudson (1924), the pupal morphology of Brontinae is described in detail for the first time. Potentially informative characters for phylogeny of larval and pupal morphology of Silvanidae are discussed.